Recent Advances in Mechanochemical Pretreatment of Lignocellulosic Biomass - Pérez-Merchán, Antonio Manuel; Rodríguez Carballo, Gabriela; Torres-Olea, Benjamín; García-Sancho, Cristina; Maireles-Torres, Pedro Jesús; Mérida-Robles, Josefa María; Moreno-Tost, Ramón (IOAP-MPDI, 2022)
Biorefineries are industrial facilities where biomass is converted into chemicals, fuels and energy. The use of lignocellulose as raw material implies the development of pretreatments to reduce its recalcitrant character prior to the processes that lead to the synthesis of the products of interest. These treatments are based on physico-chemical processes where it is necessary to use acids, bases, oxidants, and high pressure and temperature conditions that lead to the depolymerization of lignocellulose at the expense of generating a series of streams that must be treated later or to the production of by-products. In recent years, mechanochemistry is becoming relevant in the design of processes that help in the depolymerization of lignocellulose. These mechanochemical processes are being used in combination with chemicals and/or enzymes, allowing the use of minor loads of reagents or enzymes. In this review, the advances achieved in the use of mechanochemistry for treating lignocellulosic biomass or cellulose will be presented, with special emphasis on how these mechanochemical processes modify the structure of lignocellulose and help subsequent treatments. It will focus on using ball milling or extrusion, ending with a section dedicated to future work needed to implement these technologies at the industrial level.
Keywords: Mecanoquímica; Mechanochemistry; Lignocellulose; Cellulose; Ball milling; Extrusion; Depolymerization; Alkaline treatment; Acid treatment